Who should be responsible for our general well-being? A Gross National Happiness approach to promoting a responsive and sustainable business community / Dorji Wangchuk and Thinley Tobgay - Wangchuk, Dorji; Tobgay, Thinley (Universiti Teknologi Mara Selangor, 2019)
Roles and responsibilities of the business community towards society are underexplored and least understood by the business community as well as by the society in general. In the absence of any guideline on the societal responsibilities of the business community in Bhutan, an intellectual gap possibly exists between the ideology of Gross National Happiness and the roles of the business community. Thus, this review explores the tangible societal responsibilities of the business community. It also discusses the long-established arguments on the roles of business to society beyond profit-making and maximizing its financial well-being. Using keywords such as the business community, well-being, social responsibilities, Buddhist economics, western economies, and sustainable business, 114 articles were retrieved from the web-based resources. The data generated thus were analysed using the constant comparison analysis of QUAL approach. The finding indicates that the societal responsibility of the business community is an oxymoron conceptually. The paper also addresses the principles of Gross National Happiness as an approach to promoting an active and sustainable business community. However, indepth research is necessary to understand the roles and responsibilities of the business community in the context of Gross National Happiness.